The Illustrated ""A Week on the Concord and Merrimack Rivers"" - Thoreau, Henry David (Princeton legacy library., 2014)
This book offers a selection of superb photographs by the famous turn-of-the-century photographer Herbert Gleason. Retracing one of Thoreau's early journeys, Gleason produced moving and dramatic pictures of life along the rivers of New England. Originally published in 1986. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable pap.